Open data informatics and data repurposing for IBD. Issue 12 (December 2018) - Rudrapatna, Vivek; Butte, Atul
Biomedical 'big data' has opened opportunities for data repurposing to reveal new insights into complex diseases. Public data on IBD have been repurposed for novel diagnostics and therapeutics, and these datasets continue to grow. Here, we discuss the practicalities and implications of open data informatics for IBD.